THE EFFECT OF AUDIT OPINION, LOCAL GOVERNMENT SIZE, BALANCING FUNDS AND LEGISLATIVE SIZE ON THE FINANCIAL PERFORMANCE OF LOCAL GOVERNMENTS IN RIAU PROVINCE - Hashifa, Nur Shadrina; Silviani, Amanda Agnes; Ramadhan, Fitri; Danita, Irna; Rinanda, Najati; Aisyahry, Rahma Tina (Riau International Conference on Economics, Business and Accounting, 2024)
This study aims to test and analyze the Financial Performance of the Regional Government of Riau Province. Some of the factors analyzed in influencing the financial performance of local governments are audit opinion, size of local government, balancing fund, and size of the legislature.The data analysis method used in this study is Multiple Linear Regression Analysis, the data is obtained from the financial statements of the Regional Government of Riau Province in 2009-2020.The results of this study indicate that the audit opinion, the size of the local government, the balancing fund have a significant effect on the financial performance of the regional government of Riau Province, while the legislative size has no significant effect on the financial performance of the regional government of Riau Province.Kata kunci : Opini Audit, Ukuran Pemerintah Daerah, Dana Perimbangan, Ukuran Legislatif, dan Kinerja Keuangan Pemerintah Daerah.